Improving Community Skills and Economy Through the Production of Environmentally Friendly Dishwashing Soap - Irfandi, Irfandi; Murwindra, Rosa; Ahmad, Ahmad; Asmi, Weria Julia; Fiyulianti, Juni; Elvianti, Desi; Lucianti, Lucianti; Sasma, Pikran (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2026)
Soap is an inseparable product from today's household needs. This is unavoidable because soap is used frequently in everyday life. The purpose of this community service is to train the community in making dishwashing soap in Titian Modang Kopah Village, Kuantan Tengah District, Kuantan Singingi Regency, Riau Province. The production of this dishwashing soap is targeted at the Titian Modang Kopah community to be motivated to open an environmentally friendly household soap business opportunity that can provide economic benefits and can save expenses. This activity uses the participatory action research (PAR) method. The result of this community service is that the community gains increased knowledge and skills in making economical and environmentally friendly soap. This is evident from the positive response given by the community and the products resulting from the training that can be disseminated to the community. Through this community service activity, it is hoped that the community will no longer rely on commercial dishwashing soap, but instead be able to create their own. This creativity will have an economic impact on the community, as they will no longer have to spend a lot of money on purchasing dishwashing soap.